Case report: PD-L1-targeted high-affinity natural killer cells and IL-15 superagonist N-803-based therapy extend overall survival of advanced metastatic pancreatic cancer patients - Seery, Tara; Sender, Lennie; Jafari, Omid; Jones, Frank; Spilman, Patricia; Reddy, Sandeep B.; Soon-Shiong, Patrick (Frontiers in Oncology, 2025)
BackgroundMetastatic pancreatic cancer (mPC) is an aggressive form of cancer with a poor prognosis and few therapeutic options after failure of the second-line treatment. Induction of immunogenic cell death (ICD) by use of relatively low-dose chemo- or radiation therapy, enhancement of immune responses by the IL-15 superagonist N-803 (Anktiva®), and targeting of programmed death receptor ligand 1 (PD-L1)-expressing cells may offer a therapeutic approach to refractory mPC with the potential to increase overall survival (OS).MethodsFrom late 2019 to 2021, single-patient Investigational New Drug (spIND) protocols for five mPC patients were designed and approved that generally comprised combined Abraxane (nab-paclitaxel) and gemcitabine therapy with experimental therapeutics N-803, PD-L1-targeted high-affinity natural killer (PD-L1 t-haNK) cells, and aldoxorubicin, a serum albumin-binding doxorubicin prodrug. Some patients also received stereotactic body radiation therapy (SBRT), cyclophosphamide, pembrolizumab, nivolumab, and/or experimental ETBX-051 (brachyury) and/or ETBX-061 (MUC1) vaccines. Duration of spIND treatment and responses, for some patients including imaging and carbohydrate antigen 19-9 (CA19-9) levels, and OS from initial diagnosis and the start of spIND therapy were assessed.FindingsThe line/duration of spIND therapy was, for patients 1 through 5, respectively, second line/6.4 months, sixth line/3.5 months, third line/25.4 months, third line/7.4 months, and fourth line/23.2 months. OS from the commencement of spIND therapy was 13, 4.8, 26.9, 9, and 23.2 months, and OS from diagnosis was 22, 21, 42, 13, and 33 months for patients 1 through 5, respectively.ConclusionsThe OS from the initiation of spIND for all patients exceeded the reported OS for the greater-than-second-line mPC patients and, for four of five patients, second-line therapy. The OS of 13, 26.9, and 23.2 months for three patients is particularly notable. The findings here support the ongoing clinical investigations of N-803 and PD-L1 t-haNK cells in combination therapy.